Study on the Role and Contribution of Women to the Income of Fishing Families - Tambani, Grace O.; Dien, Christian Ronald; Kotambunan, Olvie Vanda (Jurnal Ilmiah Platax, 2025)
The purpose of this research is to carefully analyze the role of women in contributing to the income of fishing families in Tambun Village, Likupang Barat District. The research will be conducted in Tambun Village, Likupang Barat District, using the Purposive Sampling research method. The criteria for the respondents are: married, have a fisherman husband, and reside in Tambun Village. The total number of respondents is 20 people. Based on the research findings, there are two roles of women in Tambun Village: Public Role and Domestic Role. Furthermore, the research shows that women residing in Tambun Village, Likupang Barat District, North Minahasa Regency, contribute 49% to the total family income. This figure indicates that the income of women as fishermen's wives has not yet become a primary source of family income. This research will contribute to achieving the UNSRAT 2021-2025 Strategic Plan in the Maritime Excellence sector, focusing on the research topic of Empowerment and Increasing Women’s Participation and Social Inclusion in the Maritime Environment. Keywords: Women's roles, family income, Tambun Village, tourism. Abstrak Tujuan penelitian ini adalah untuk menganalisis dengan cermat berapa besar peran perempuan dalam berkontribusi terhadapat pendapatan keluarga nelayan di Desa Tambun Kecamatan Likupang Barat. Lokasi penelitian akan dilaksanakan di Desa Tambun Kecamatan Likupang Barat dengan menggunakan metode penelitian Purposive Sampling, kriteria responden yaitu : sudah berumah tangga dan bersuamikan seorang nelayan dan tinggal di Desa Tambun. Jumlah responden berjumlah 20 orang. Berdasarkan hasil penelitian terdapat 2 Peran Perempuan didesa Tambun yaitu Peran Publik dan Peran Domestik selain itu berdasarkan penelitian terlihat bahwa perempuan yang bermukim Desa Tambun Kecamatan Likupang Barat Kabupaten Minahasa Utara berkonrtibusi sebesar 49 % terhadap total pendapatan keluarga. Nilai ini menunjukkan bahwa pendapatan perempuan sebagai isteri nelayan belum menjadi tumpuan pendapatan keluarga. Penelitian ini akan berkontribusi pada pencapaian RENSTRA UNSRAT 2021 – 2025 di Bidang Unggulan Kemaritiman yang difokuskan pada topik riset Pemberdayaan dan Peningkatan Partisipasi Perempuan dan Inklusi Sosial dalam Lingkungan Kemaritiman. Kata kunci : Peran perempuan, pendapatan keluarga, Desa Tambun, Pariwisata.